2017
DOI: 10.3390/medicines4030063
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Three Essential Oils of the Lamiaceae Family

Abstract: Herbs and spices have been used since ancient times to improve the sensory characteristics of food, to act as preservatives and for their nutritional and healthy properties. Herbs and spices are generally recognized as safe (GRAS) and are excellent substitutes for chemical additives. Essential oils are mixtures of volatile compounds obtained, mainly by steam distillation, from medicinal and aromatic plants. They are an alternative to synthetic additives for the food industry, and they have gained attention as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 56 publications
(64 reference statements)
3
140
1
13
Order By: Relevance
“…Oregano plants are known to possess a special composition of Essential Oil (EO) which is of great interest for pharmaceutical and industrial market [5,6]. Furthermore, it was grouped into different chemotypes: Acyclic, cymyl, bicyclic, and/or bornane type compounds depending on the predominance of particular components as (a) linalool, linalyl acetate, β-ocimene and myrcene; (b) p-cymene, γ-terpinene, pcymene-8-ol, thymol methyl ether, carvacrol methyl ether, thymoquinone, thymol and carvacrol; (c) sabinene, trans-/cissabinene hydrate and their acetate; and (d) camphor, borneol, bornyl acetate, respectively [1, 4, 7 -10].…”
Section: Introductionmentioning
confidence: 99%
“…Oregano plants are known to possess a special composition of Essential Oil (EO) which is of great interest for pharmaceutical and industrial market [5,6]. Furthermore, it was grouped into different chemotypes: Acyclic, cymyl, bicyclic, and/or bornane type compounds depending on the predominance of particular components as (a) linalool, linalyl acetate, β-ocimene and myrcene; (b) p-cymene, γ-terpinene, pcymene-8-ol, thymol methyl ether, carvacrol methyl ether, thymoquinone, thymol and carvacrol; (c) sabinene, trans-/cissabinene hydrate and their acetate; and (d) camphor, borneol, bornyl acetate, respectively [1, 4, 7 -10].…”
Section: Introductionmentioning
confidence: 99%
“…This might explain the fact that the synergistic or antagonistic effect of one compound in the EO content has to be taken into account even though it exists in a minor percentage in the composition of the mixture. This information in the literature should be remembered, too, although the antimicrobial activity of the EOs is attributed mainly to their main compounds in their contents [31].…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial potency of carvacrol and its isomer thymol, has been reported with extremely low minimum inhibitory concentration and minimum bactericidal concentration values (Qaralleh et al, 2009;Althunibat et al, 2016). Carvacrol is considered as one of the most bactericidal essential oil components against both Gram positive and Gram negative bacteria (Hammer et al, 1999;Nieto, 2017). Mihajilov-Kristev et al, showed that essential oil (Satureja hortensis) rich in carvacrol (67%) and γ-terpinene (15%) are strong bacteriostatic and bactericidal agent against both Gram positive and Gram negative bacteria with low minimum inhibitory concentration and minimum bactericidal concentration values (0.025-0.78 μL/mL) (Mihajilov-Krstev et al, 2010).…”
Section: The Chemical Composition Of Essential Oil Of Variousmentioning
confidence: 99%